The Uniqueness of Short-Term Collateralization - Klapper, Leora (World Bank, Washington, DC, 2013)
The author finds evidence that lines of credit secured by accounts receivable are associated with business borrowers with a high risk of default. While an unsecured short-term loan is repaid from the borrower's future cash flow, a loan secured by accounts receivable (a unique form of "inside" collateral) is repaid from previously generated and observed sales (the borrower's trade credit terms to its customers). Consequently, lenders that secure accounts receivable are most concerned with the credit risk of the borrower's customers and the borrower's ability to continue to generate new sales. A stylized theoretical model demonstrates that the value of a secured line-of-credit loan in minimizing contracting costs is associated with the borrower's business risk and the quality of the borrower's customers. Empirical tests on a sample of publicly traded U.S. manufacturing firms find that firms with secured line of credit loans are observably riskier and have fewer expected growth opportunities. The author's findings suggest that observably riskier borrowers can borrow more on a secured than on an unsecured basis. The results highlight the important role of secured letters of credit in providing liquidity to risky, credit-constrained firms that might not have access to external financing through other channels.